Herb-induced hepatitis secondary to artemisinin: A case report - Zhan, Jiwei; Ding, Meilin; Li, Jin; Su, Lei (Frontiers in Medicine, 2022)
This report describes a rare case of severe liver injury secondary to a herbal supplement containing artemisinin. The patient received plasma exchange with bilirubin filtration adsorption therapy. The case is unique in its severe cholestasis. Bilirubin decreased to baseline after 62 days. This will help to improve clinicians' awareness of the diagnosis and treatment of drug-induced liver injury.